Analisis Karya Fotografi Pieter Hugo Rwanda #14 - Winata Faturahman (Institut Seni Indonesia Yogyakarta, 2022)
Portrait photography is photography with the subject of the person being photographed closely. This type of photography generally emphasizes expression to convey a message. Referring to this information, portrait photography is one of the media for displaying visual messages with human subjects/people. Pieter Hugo is a portrait photographer whose focus is on Africa. Various works produced mostly highlight life in Africa. Pieter Hugo's photo entitled Rwanda #14 is a photo with a high angle shot. In the photo visualizing an African boy lying on a meadow in the photo from above. The photo is Pieter Hugo's work in the 1994 editorial where the photo works in the editorial are Pieter Hugo's expression of the genocide that hit Africa in 1994. The purpose of this research is to contribute to the world of literacy, especially literary work. photography. Because photography is a medium that can be used as a messenger through visuals that can be a unit of analysis to be researched. The research method used in this study is a qualitative method. The selection of qualitative methods was chosen because the qualitative method is a method that can be used to analyze the object of research.